Clonagem e expressão heteróloga de PnTx2-6, uma toxina ativa na função erétil: obtenção e caracterização parcial de seus mutantes - Fernanda Silva Torres (2011)
The venom of Brazilian armed spider, Phoneutria nigriventer, contains several toxins; many of them are active on ion channels and other receptors of mammals and insects. Accidents involving humans are characterized by various symptoms including: neurotoxicity, intense pain, sudoresis, agitation, salivation, priapism, cardiac perturbations characterized by tachycardia, arrhythmia and death. Priapism is a painful and involuntary erection of the penis that is also induced by the purified toxins PnTx2-5 and PnTx2-6. In addition, electrophysiological studies have shown that these toxins slow down the inactivation current of sodium channels. Our group has studied the effects of PnTx2-6 in erectile function of rats and mice. It has shown that PnTx2-6 potentiates the erectile function in normotensive rats and fully or partially restored the erectile function of DOCA-salt hypertensive rats, stz-diabetics and old mice. The effects of PnTx2-6 on erectile function are shown to be mediated by NO that increases in the presence of this toxin. These results suggest that PnTx2-6 could be an important tool for the development of new pharmacological agents for the treatment of erectile dysfunction. As the toxin is produced in low quantity in the spiders venom gland, this is a limiting factor for studies. Therefore, the recombinant production of this toxin is of great interest providing it to a range of experimental approaches. In this study, the encoding region of the PnTx2-6 toxin was cloned and expressed as thioredoxin fusion protein in the cytoplasm of E. coli. After purification and cleavage, tests in vivo indicated that the recombinant toxin presents activity similar to that of the native toxin and the Western-Blotting analysis revealed that the anti-venom antibody of Phoneutria nigriventer is reactive against recombinant toxin. The effect of rPnTx2-6 in the erection function was evaluated through changes in intracavernosal pressure/mean arterial pressure ratio (ICP/MAP) during electrical stimulation of the major pelvic ganglion of normotensive rats. Subcutaneous injection of rPnTx2-6 (12g/kg), as the natural peptide, potentiated the ICP/MAP induced by ganglionic stimulation. The rPnTx2-6 fusion protein increased the glutamate release by cortical synaptosomes in the rat brain. We also obtained mutant fusion proteins to check for the key role of certain amino acid residues in the toxin action, as previously suggested by molecular modeling. The mutants were constructed from in vitro synthesis by using specific primers that flanked the regions of mutations. The recombinant vector pET32c(+)-PnTx2-6, previously cloned, was used as a template for mutations. The mutant plamids were transformed in E. coli, sequenced, and expressed as thioredoxin fusion proteins. The mutant fusion proteins were purified (affinity and gel filtration chromatographies). To date, six mutants were idealized (Y35N; Y35A; W37L; W37A; Y35NW37L; Y35AW37A). Five (Y35N; Y35A; W37L; W37A; Y35AW37A) were sequenced (DNA), purified, and their molecular masses were determined. The mutant fusion proteins, comparative with native toxin and recombinant fusion proteins, were tested for their effect on glutamate release. All the mutants were less effective in releasing glutamate compared to the native toxin PnTx2-6 and recombinant fusion protein rPnTx2-6. In conclusion,we expressed the rPnTx2-6 active and some of its mutants (Y35N; Y35A; W37L; W37A; Y35AW37A) evidencing the key role of some amino acid residues implied in the biological activity of this toxin.